Policy and Practice Gap in Continuous Assessment System Provisioned Under Integrated Curriculum - Prajapati, Pancha Laxmi (Ganeshman Darpan, 2024)
Continuous assessment system has been taken as an integral part of teaching learning process of school education in Nepal for a few decades. It is an approach used by teachers during their instructional process to strengthen students’ learning as intended by official curricula including integrated curriculum proposed for grades 1 to 3. Formative evaluation enables teachers to collect, analyze, and use students’ information to make teaching and learning process more effective and productive through regular feedback mechanism. But this evaluation has not been practiced by teachers in real classroom situations in spite of having rigor policy provisions. In this regard, this study entitled ‘Policy and Practice Gap in Continuous Assessment System Provisioned under Integrated Curriculum’ aimed at determining the understanding and practices of continuous assessment system and policy and practice gap in continuous assessment system in low performing to high performing government schools located in Bhaktapur district. This study utilized qualitative research design and interpretative paradigm. The whole research process in this study was guided by two objectives and devised under interpretive paradigm followed by basic qualitative research design. Six public schools (two high performing, two averages performing, and two low performing), six head-teachers, eighteen teachers, and eighteen teaching classes were chosen as study samples by using purposive sampling technique. Furthermore, in-depth interviews, classroom observations were used as main techniques to gather qualitative information required to answer the objective of study.